Penerapan Kode Golay Diperpanjang pada Kriptosistem McEliece - Ilham Setyawan; Putranto Hadi Utomo (STMIK Budi Darma, 2022)
In this modern era, quantum computers appear that can calculate mathematical operations faster than classical computers. Some cryptosystems can be solved with the computer, but there are cryptosystems that have not been solved using the computer, one of which is the McEliece cryptosystem. The McEliece cryptosystem uses error correction codes so that it is more secure than cryptosystems that use factorization. The basic idea of this cryptosystem is that someone can give an error message so that the message cannot be read by an attacker. Golay code is a code with a length of 24-bits that can correct errors up to 3 bit errors. This article describes the implementation of Golay code on the McEliece cryptosystem.